Role of genome technology in dairy food quality and safety - De, Sachinandan (Indian Journal of Dairy Science, 2019)
Genomics tools, specifically the different affordable Sequencing methods, are rapidly transforming almost every aspect of Biological Sciences including food science. Applications of genomic technologies in food sciences is generally considered a great leap forward with some concerns regarding the need of well-equipped and trained laboratories to discriminate between good and bad micro-organisms in the fermented food stuff. Species identification of raw and finished dairy and animal products has become an important issue regarding the assessment of food composition. Protection against species substitution or admixture in dairy and animal products is of significant importance for reasons relating to consumer preference, public health and government regulations. Milk and milk products are of particular interest, because they are a group of foods that play an important role in feeding the population and are essential for certain groups of consumers (women, children, and the elderly). Milk products are often prone to adulteration practices, since milk is a fairly expensive raw material and can be easily replaced in part by other dairy or non-dairy ingredients. DNA based methods became very popular, since they are considered more reliable as a result of DNA stability under high temperatures, pressures and chemical treatments used during processing of food products. The polymerase chain reaction (PCR) is the most widely used molecular technique, because of its simplicity, sensitivity and reproducibility. Ruminant milk can be easily used as a source of DNA, since it has a large amount of somatic cells, mostly leucocytes but also epithelial cells from the milking mother, which contain genomic DNA suitable for any kind of genomic DNA testing. PCR amplification of various regions of mitochondrial genome, 12S rRNA, growth hormone (GH) gene and PCR RFLP have been reported and proved the sensitivity of DNA based methods and their reliability for species identification in a wide range of raw and finished animal food products. Complete genome sequencing of bacterial isolates (pathogenic or lactic acid bacteria) has started to replace contemporary popular molecular methods, like ribotyping, MLST and Pulse Field Gel Electrophoresis (PFGE), as subtyping method of choice. Whole Genome Sequencing can able to route of transmission in case of increasingly smaller outbreaks.